Laboratory Investigation of Energy Propagation and Scattering Characteristics in Cylindrical Rock Specimens. (24th September 2018) - Chen, Lu; Qiao, Lan; Yang, Jianming; Li, Qingwen
Abstract : Deep mining involves complex geological environments. Moreover, along with strong disturbance, rockbursts and other severe dynamic hazards can occur frequently. Energy theory is widely regarded as the most appropriate method for understanding the mechanism of deep dynamic problems. When modeling dynamic disasters, energy theory includes the energy storage, energy accumulation, and energy transfer. To study the energy transfer characteristics in rock, a series of split-Hopkinson pressure bar (SHPB) impact tests were conducted with long granite specimens (400 mm in length and 50 mm in diameter) and modified incidence bars (having the same cross-sectional area but different shapes). The test results indicate that the impact energy decays exponentially with an energy attenuation coefficient of −0.42. For the scattering characteristics of energy in the rock, the scattering distance is found to be approximately three times the specimen diameter, which is very similar to Saint-Venant's principle in elastic mechanics.